2014
DOI: 10.1103/physrevlett.113.023004
|View full text |Cite
|
Sign up to set email alerts
|

Simplest Molecules as Candidates for Precise Optical Clocks

Abstract: The precise measurement of transition frequencies in cold, trapped molecules has applications in fundamental physics, and extremely high accuracies are desirable. We determine suitable candidates by considering the simplest molecules with a single electron, for which the external-field shift corrections can be calculated theoretically with high precision. Our calculations show that H(2)(+) exhibits particular transitions whose fractional systematic uncertainties may be reduced to 5×10(-17) at room temperature.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
139
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(148 citation statements)
references
References 39 publications
7
139
0
1
Order By: Relevance
“…Recently, the precision of relativistic and radiative energy corrections to the nonrelativistic energies was strongly improved. With the inclusion of the full set of contributions of order mα 7 and leading-order terms of order mα 8 , the relative uncertainty is now below 4 × 10 −11 .…”
Section: Calculation Of Ro-vibrational Frequency Transitions In Hd +mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the precision of relativistic and radiative energy corrections to the nonrelativistic energies was strongly improved. With the inclusion of the full set of contributions of order mα 7 and leading-order terms of order mα 8 , the relative uncertainty is now below 4 × 10 −11 .…”
Section: Calculation Of Ro-vibrational Frequency Transitions In Hd +mentioning
confidence: 99%
“…Optical clocks based on trapped atomic ions have shown that laser spectroscopy at very high accuracy (below one part in 10 17 ) is possible [6]. Recent theoretical studies point out that also for molecular hydrogen ions experimental uncertainties in the 10 −16 range should be possible [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, to the best of our knowledge no dipole-forbidden vibrational-that is, IR-spectra of molecular ions have been reported so far. Studies of vibrational transitions in molecules, however, are attractive as they probe different spectral domains and dynamic regimes from those in studies of atomic systems 5,8,12 .Dipole-forbidden vibrational transitions in molecules 13 are several orders of magnitude weaker than dipole-forbidden optical transitions typically used in atoms 2,3 , rendering their observation challenging. Thus far, they were observed only in a handful of neutral diatomics, such as H 2 , N 2 and O 2 , using high-pressure samples and/or very long absorption path lengths [14][15][16] .…”
mentioning
confidence: 99%
“…By contrast, to the best of our knowledge no dipole-forbidden vibrational-that is, IR-spectra of molecular ions have been reported so far. Studies of vibrational transitions in molecules, however, are attractive as they probe different spectral domains and dynamic regimes from those in studies of atomic systems 5,8,12 .…”
mentioning
confidence: 99%
See 1 more Smart Citation